2006
DOI: 10.4269/ajtmh.2006.74.573
|View full text |Cite
|
Sign up to set email alerts
|

ASSOCIATION OF FCγ RECEPTOR IIA (CD32) POLYMORPHISM WITH MALARIAL ANEMIA AND HIGH-DENSITY PARASITEMIA IN INFANTS AND YOUNG CHILDREN

Abstract: Protective immunity against Plasmodium falciparum is partially mediated through binding of malaria-specific IgG antibodies to Fcgamma receptors. Polymorphic variability in Fcgamma RIIa (H/R-131) is associated with differential binding of IgG subtypes and malaria disease outcomes. However, the role of Fcgamma RIIa-131 variability in conditioning susceptibility to severe malarial anemia, the primary manifestation of severe malaria in holoendemic P. falciparum transmission areas, is largely undefined. Thus, Fcgam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 22 publications
5
47
1
1
Order By: Relevance
“…While one study found that the H/R genotype is more common in children at risk for severe malaria (50), other studies have shown an association between the H/H genotype or the H allele and severe malaria (10,38). Yet others have found no association (39) or that the H/H genotype is protective (33). The discrepancy in results likely comes from differences in study design, ethnic groups studied, and the pattern of malaria transmission at each study site.…”
Section: Cd16mentioning
confidence: 63%
“…While one study found that the H/R genotype is more common in children at risk for severe malaria (50), other studies have shown an association between the H/H genotype or the H allele and severe malaria (10,38). Yet others have found no association (39) or that the H/H genotype is protective (33). The discrepancy in results likely comes from differences in study design, ethnic groups studied, and the pattern of malaria transmission at each study site.…”
Section: Cd16mentioning
confidence: 63%
“…API biochemical galleries (bioMéri-eux, Inc.) and/or serology was used for identification of blood-borne bacterial isolates. The presence of the sickle cell trait (HbAS) was determined by cellulose acetate electrophoresis, while glucose-6-phosphate dehydrogenase (G6PD) deficiency was determined as previously described (47).…”
Section: Methodsmentioning
confidence: 99%
“…Since previous geneticsbased studies have thoroughly investigated SNPs (41,47) and haplotypes (40,46), we investigated the effect of cross-SNP combinations in conditioning SMA. We examined the associations between Fc␥RIIIA (Ϫ176F/V) and TLR9 (Ϫ1237T/C) promoter-variant combinations and susceptibility to SMA (Hb Ͻ 6.0 g/dl) in children (aged 3 to 36 months) residing in this area of western Kenya where P. falciparum transmission is holoendemic.…”
mentioning
confidence: 99%
“…To more fully elucidate the potential importance of SCGF in human malaria, variation in the SCGF promoter was explored, a strategy we have previously used in western Kenya to identify immune response genes that condition susceptibility to pediatric SMA (3,35,37,38). Although to date, no studies have described the effect of polymorphic variability in SCGF on any disease, we focused on a single nucleotide polymorphism (SNP) in the promoter region (Ϫ539C/T; rs7246355) based on the allelic distribution in the Yoruba in the Ibadan population in Nigeria examined as part of the HapMap (phase 3) project.…”
mentioning
confidence: 99%